2020
DOI: 10.1002/ajp.23210
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of the red‐handed howler monkey (Alouatta belzebul) in amazonian savannas is related to forest patch area and density of flooded area palms

Abstract: All Neotropical primates are arboreal and thus depend on forests for their survival. Arboreality puts many Neotropical primates at risk of extinction due to the high rates of deforestation in the tropics. We assessed the influence of vegetation structure and forest patch attributes on the occurrence of the threatened redhanded howler monkey (Alouatta belzebul) in an Amazonian savanna. Using a sample of 38 forest patches in a region of approximately 2000 km 2 in the state of Amapá, northern Brazil, we used logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
3
0
3
Order By: Relevance
“…These populations tended to stay away from serious eco-tourism areas in the core zone. Many studies have shown that environmental variables such as elevation, slope, aspect, and forest cover significantly affect animal distribution [ 57 , 58 , 59 , 60 ]. This study also supports those findings.…”
Section: Discussionmentioning
confidence: 99%
“…These populations tended to stay away from serious eco-tourism areas in the core zone. Many studies have shown that environmental variables such as elevation, slope, aspect, and forest cover significantly affect animal distribution [ 57 , 58 , 59 , 60 ]. This study also supports those findings.…”
Section: Discussionmentioning
confidence: 99%
“…A população amazônica tem seu limite oriental na Mata dos Cocais, nos estados do Maranhão e Tocantins, onde a distribuição geográfica coincide com os limites do bioma Amazônico. O rio Xingu pode ser o limite ocidental e, ao norte, a espécie é limitada pelo baixo Amazonas, embora haja registro de populações no Amapá (Silva et al, 2013;Silvestre et al, 2020). R. Hilário (com.…”
Section: Distribuiçãounclassified
“…Alouatta belzebul ocorre em Floresta Tropical Amazônica de Planície, Floresta de Várzea e fragmentos de Floresta Tropical Atlântica do Nordeste (Veiga et al, 2008;Silvestre et al, 2020). Não é restrito a hábitats primários e apresenta tolerância a modificações/perturbações no ambiente, sendo encontrado em áreas perturbadas pela extração mineral (Carvalho, 2010) e ocupando fragmentos de tamanho reduzido e em regeneração (Ludwig et al, 2020).…”
Section: Distribuiçãounclassified
See 1 more Smart Citation

Ficha de Alouatta belzebul

Mônica Mafra Valença-Montenegro,
Francisco Virgínio de Souza,
Ítalo Mourthé
et al. 2024
Datasets - Sistema SALVE - ICMBio
“…Low flooded forests are considered key habitats for various species because their proximity to non-flooded forests favors the seasonal provision of fruits to a large number of animals (Silvestre et al 2020), and due to their distinct floristic composition and phenology (Carretero & Defler 2016). Few studies have described the structure and floristic diversity of low flooded forests (Chiquini et al 2017).…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%